International development issues and challenges - Kingsbury, Damien; McKay, John; Hunt, Janet; McGillivray, Mark; Clarke, Matthew (Palgrave Macmillan, 2012)
"This text provides a critical interdisciplinary introduction to the theory, practice and study of development. The thoroughly revised and updated new edition takes account of the impact of the global financial crisis, the economic rise of China and India and the further ramifications of global warming"--Provided by publisher.